(untitled) (Journal of Philosophy Culture and Political Science, 2025)
This article examines the theoretical foundations of political values and their impact on political, social, cultural, and economic changes in society. The aim of this study is to demonstrate the significance of political values as a driving force of political actions and as a factor shaping a prospective model of social structure under conditions of radical social changes. The scientific and practical significance of the research lies in showing the impact of political values on the sustainable development of society and the strengthening of political pluralism. Political values play a crucial role in society and form the foundation of the political structure. This study comprehensively analyzes the theoretical and practical aspects of political values in the contemporary state of society, their differences, and developmental trends. The research methodology involves a scientific-theoretical analysis of the works of foreign and domestic scholars on political values. These methods allowed for the identification of leading ideas and political views of the populace regarding political values. The results of the study showed that political values represent a complex social phenomenon and are closely associated with generational differences in viewpoints. Additionally, despite the limited research on political values in Kazakhstan, significant studies are currently being conducted in this area. The value of the research lies in uncovering the main mechanisms of formation and development of political values in Kazakhstan, as well as in the comprehensive analysis of the impact of these values on society as a whole. The practical significance of the study’s results contributes to the improvement of policies aimed at developing political values and strengthening political culture in society. Keywords: value, political values, value system, social phenomenon, democratic society, cultural factors, social transformation.